ANALISIS KUALITAS PELAYANAN PERAWAT UNTUK MENINGKATKAN KEPUASAN KLIEN DI RSI SITI HAJAR SIDOARJO - jurnalpps pps; Edi Yuwono; C. Sri Hartati; Ruddy Winarko (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
This study aims to determine the quality of service nurses at Islamic Hospital (RSI) Siti Hajar Sidoarjo, supporting factors, inhibiting factors and service strategies nurse service quality development at RSI Siti Hajar Sidoarjo. In this study, researchers used descriptive research with a qualitative approach. That is, data collected from depth interviews, field observations, and related documents. Data analysis in this study using three components consisting of data reduction, data presentation, and conclusion. In this study researchers in the analysis by using triangulation to check the validity of data / test data credibility. The results showed that the quality of nurse service at Islamic Hospital (RSI) Siti Hajar Sidoarjo is generally good, in terms of tangible dimension, reliability, responsiveness, assurance, emphathy, although there are still some shortcomings or complaints, but all informants stated that the nurse service at Islamic Hospital (RSI) Siti Hajar Sidoarjo is good. Keywords: service quality, nurse